WOMEN-PANCHAYAT-ELECTIVES AT THE INTERFACE OF STATE AND VILLAGE POLITICS: Gendered Constructions of the Political Space - Stefanie Strulik
This paper considers gram panchayat councils as an interface of the local village community with the state. Gram panchayat councils are bodies of self-governance at the village level in India and constitute the lowest tier of the reformed and e-institutionalized Panchayati Raj System. After the 73rd and 74th constitutional Amendments in the early 1990s and their attempts to democratize the existing political and administrative structures by prescribing, amongst many other reforms and reservations, a 1/3rd women's quota for all Panchayati Raj bodies and offices, a great number of women made inroads into the local, hitherto almost exclusively male political arena. Based on empirical fieldwork of almost two years, this paper will look into the changes brought upon the local political arena by the political participation of women. Thereby it will focus particularly on the subtle changes in gendered structuration of the political space. It will be argued that by women's political participation, i.e. women's prioritizations and agenda setting, women's working styles or ways of "doing politics", gendered knowledge-systems and gendered support-systems, as well as gendered modes of interaction - the political space gets transformed. However, the new meanings and the feminization of the political space are highly contested and have to be again and again negotiated and defended not only vis--vis state authorities and other members of the panchayat system, but also within the village community. The paper will give special emphasis to the role state officials' support or non-cooperation, governmental guidelines, available governmental schemes or regulations and governmental training programs play concerning the women-electives' appropriation and transformation of the political space and thus eventually with regard to changing gender relations.